2017
DOI: 10.21608/jva.2017.37166
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Milk Thistle Extract against Renal Toxicity Induced By Diethylnitrosamine and Carbon Tetrachloride in Adult Rats

Abstract: The rapeutic effects of milk agains t renal toxicity in rats Ahmed and Tag

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…These results indicated a profound activation of HSCs in response to DEN+CCl4 intoxication. Similarly, previous studies showed that α-SMA expression as well as collagen and hydroxyproline content were significantly elevated in response to injection with CCl4 alone or in combination with DEN ( Mansour et al, 2010 ; Abdel-Moneim et al, 2015 ; Ahmed and Tag, 2017 ).…”
Section: Discussionsupporting
confidence: 71%
“…These results indicated a profound activation of HSCs in response to DEN+CCl4 intoxication. Similarly, previous studies showed that α-SMA expression as well as collagen and hydroxyproline content were significantly elevated in response to injection with CCl4 alone or in combination with DEN ( Mansour et al, 2010 ; Abdel-Moneim et al, 2015 ; Ahmed and Tag, 2017 ).…”
Section: Discussionsupporting
confidence: 71%